35 London Ambulance Service and Palliative Partners – Increasing confidence to care for dying patients at home. (14th March 2023) - Taylor, Ros; Laverty, Di; Murphy-Jones, Georgina; Thorpe, Josh; Burke, Ruth
Abstract : Background: The ECHO methodology is an international initiative aiming to cultivate communities of practice, with reciprocal knowledge and confidence transfer between a specialist hub and stakeholder teams. This project was established to enhance the confidence of London Ambulance Service clinicians who are increasingly required to attend dying patients, and manage them at home. The 'stakeholders' were all grades of ambulance clinicians. The hub consisted of a palliative physician and nurse, a care home matron, a GP, plus two end of life leaders from London Ambulance Service (LAS) and an administrative partner (MyHealth Hillingdon). Method: The curriculum was collaboratively agreed with LAS. Topics included understanding the palliative approach, ethical decision-making, symptom control for those patients who want to stay at home, emergencies at the end of life, communication challenges and family dynamics. Structure included brief didactic learning, real-time polls and case presentations by ambulance clinicians. Results: Engagement has been huge with over 200 ambulance clinicians engaging with the first three ECHO sessions. Initial themes from the contemporaneous realist evaluation using Slido demonstrate key changes in attitude, knowledge gaps, confidence and engagement. Learnings such as the following: 'Do no harm' doesn't just apply to the patient...are we also trying to consider family/ourselves/the wider healthcare system' 'Dealing with different family opinions about whether hospital is appropriate' 'Services available to avoid hospital admission for patient comfort' 'Gives me a lot more confidence to have the challenging conversations with family if I recognise a patient is near end of life' Conclusion: The ECHO methodology, with a strap line 'all teach, all learn', is confirmed as a successful structured approach to cascade information in all directions to enhance practice and confidence for ambulance clinicians. Formal evaluation at the end of the first curriculum will take place, with a view to how to sustain ongoing learning.